ACADEMIC REPRESENTATIONS OF THE FAMILY IN DOCTORAL RESEARCH: A COMPARATIVE STUDY OF TURKEY AND GERMANY (2019–2024) - Bora Başaran (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study examines the representation of “family” in doctoral theses produced in Turkey and Germany in the field of social sciences from 2019-2024, with an eye toward implications for education, curriculum, and teacher education. Using a mixed-methods approach that combines bibliometric mapping and title-based content analysis, this study studied over 300 German and Turkish doctoral dissertations found in the Deutsche Nationalbibliothek and Council of Higher Education Thesis Center of Türkiye, respectively. The study reviews disciplinary prevalence, thematic subfields, and methodological frameworks to determine how family is conceptualized in two IDR academic traditions. Initial analysis reveals that Turkish dissertations largely center on family in the field of education sciences and sociology, also tracking themes like value transmission, intergenerational dynamics, and family-school collaboration. In contrast, the German dissertations are primarily aligned to psychology and social work, focusing on migration, multiculturalism, and integration in educational contexts. The uniqueness of this study comes from the cross-national dataset and the comparative methodology to develop understanding about emerging post-pandemic themes such as digitalization, family assistance for remote education, and cultural adjustment. The study then explains how a “Comparative Academic Trends Map,” develops policy-relevant knowledge and understanding for curriculum developers, teacher educators, and education policymakers. The results can provide insight into the larger conversation regarding international and comparative education, and can also support the Turkey 2025 “Family Year” initiative and the Turkey Century Curriculum Model, both of which situate the family in education. Presenting this project demonstrates ways in which doctoral research supports culturally relevant curricula, strengthens teacher education, and create opportunities for cross-national dialogue on the changing role of families in education systems.